2012
DOI: 10.1186/1755-8166-5-13
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 22q11.2 microdeletion in monozygotic twins with discordant phenotype and deletion size

Abstract: We report on a pair of male monozygotic twins with 22q11.2 microdeletion, discordant phenotype and discordant deletion size. The second twin had findings suggestive of DiGeorge syndrome, while the first twin had milder anomalies without any cardiac malformation. The second twin had presented with intractable convulsion, cyanosis and cardiovascular failure in the fourth week of life and expired on the sixth week of life, whereas the first twin had some characteristic facial appearance with developmental delay b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 34 publications
0
26
0
2
Order By: Relevance
“…However, Rauch et al (2005) demonstrated a correlation between deletion characteristics and phenotypic expression by assessment of individuals with typical and atypical 22q11.2 deletions, showing that atypical CHD and mild dysmorphism are recognizable feature of atypical distal deletions [20]. Recently, a case-report of monozygotic twins differing in their deletion size and clinical expression was published, indicating a possible role of deletion characteristics for the phenotype [31]. …”
Section: Discussionmentioning
confidence: 99%
“…However, Rauch et al (2005) demonstrated a correlation between deletion characteristics and phenotypic expression by assessment of individuals with typical and atypical 22q11.2 deletions, showing that atypical CHD and mild dysmorphism are recognizable feature of atypical distal deletions [20]. Recently, a case-report of monozygotic twins differing in their deletion size and clinical expression was published, indicating a possible role of deletion characteristics for the phenotype [31]. …”
Section: Discussionmentioning
confidence: 99%
“…22q11DS is characterized by variable expressivity, and phenotypic discordance between monozygotic twins (McDonald-McGinn, 2001; Halder, Jain, Chaudhary, & Varma, 2012). In light of the variable expressivity, it is important to identify clinical correlations between cardinal features.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a high resolution single nucleotide polymorphism (SNP)-array allowed for the detection of copy number variants (CNVs) as well as SNPs. Halder et al (12) reported a case in which twins carrying the 22q11.2DS microdeletion had discordant phenotypes with a different sized genetic deletion. Another technique, exome sequencing, offers an efficient and affordable method to investigate the genetic factors involved in human diseases (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%